MOTIVATIONS TO IMPLEMENT SUSTAINABLE WAREHOUSE MANAGEMENT: A LITERATURE REVIEW - Siti Norida Wahab; Sharul Shahida Shakrein Safian; Norashida Othman; Nur Azirah Zahida Mohamad Azhar (International Journal of Accounting, Finance and Business, 2021)
Green supply chain management defines as integrating green and sustainable practices into supply chain management. Due to the current environmental pollution, companies realized that the concepts of green and sustainability are the focal values towards creating a competitive advantage. Green and sustainability are also the main values in implementing sustainable warehouse management (SWM) towards reducing environmental issues and increasing social responsibility. This conceptual paper aims to observe motivations to implement SWM because this area is gaining recognition and the findings can be used for future research. This paper is based on a comprehensive literature review to discover motivations to implement SWM. Customer demand, market competition, government support, certification, management support, asset specificity, and information technology are the motivations to implement SWM. This paper only discusses the motivations related to the SWM and ignoring other forms of sustainable practices. Plus, this paper only concerns on English literatures and omits other languages. Due to the lack of empirical evidence, future research should be done to test the motivations relevancy. This study addresses stakeholders of the SWM, which have not been entirely recognise and acknowledge. This conceptual paper adds value to the knowledge of the SWM and serves as useful information to both scholars and practitioners.